(untitled) (Homoeopathy for All, 2025)
Tinea corporis (TC) is the most prevalent superficial fungal infection of the skin, caused by dermatophytes that colonize and thrive on dead keratin within the epidermis. This condition is characterized by distinctive ring shaped lesions, often accompanied by itching, redness, and discomfort. Various environmental factors, including excessive heat, high humidity, and tight-fitting clothing, create favorable conditions for fungal proliferation, exacerbating the infection and increasing the likelihood of recurrence. The persistent nature of TC not only leads to physical distress but also affects a patient’s psychological well-being, self-confidence, and overall quality of life. Therefore, effective treatment approaches that target both the underlying cause and aggravating factors are crucial for long-term relief and improved patient outcomes. Case Summary: This case of TC, with extensive spread on the body, demonstrates the curative effect of homoeopathic medicine. A 40 year-old female diagnosed with TC was treated successfully with individualised homoeopathic medicine for six months. The outcome was assessed through before-and-after-treatment photographs. The case has been reported as per HOM-CASE guidelines. A complete alleviation of TC was observed with homoeopathic medicine pulsatilla.